A Ca2+-activated potassium channel (BKCa) in Leydig cells is involved in testosterone production - Siebert, S. (2011)
Previously, we found that human steroid-producing ovarian granulosa cells express all major types of Ca2+-activated potassium channels (KCa), including BKCa, IK and SKs (Traut et al., RB&E, 2009), and that modulation of the activity of these channels resulted in alteration of steroid production. In the male gonad Leydig cells produce androgens, but whether these cells are endowed with KCas is not known. We addressed these points and focussed on BKCa, which is Ca2+-activated and the underlying channel for a prominent current. It can be manipulated, e.g. by a specific blocker, the red scorpion toxin iberiotoxin (IbTx), which binds to the outer face with high affinity and selectively inhibits the current by decreasing both the probability of opening and the open time of the channel.